2017
DOI: 10.1163/22244662-06301001
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of heat shock protein 70 (Hsp70) levels in the bdelloid rotifer Rotaria rotatoria under temperature stress

Abstract: The bdelloid rotifer is an important component of freshwater zooplankton, exhibiting the features of parthenogenesis and anhydrobiotic capability. Heat shock proteins (Hsps), acting as molecular chaperones, are a highly conserved, ubiquitously expressed family of stress response proteins. In this study, the thermal optimums for heat-shock response and the levels of Hsp70 in Rotaria rotatoria (bdelloid rotifer) under different stress conditions were evaluated using survival assays and western blotting with fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…( 2013 ) found that the upregulation of CuZn‐SOD gene expression in a certain range plays an important role in maintaining the physiological equilibrium of Brachionus calyciflorus . In addition, stress proteins such as heat shock proteins and antioxidant enzymes also play an important role in protecting zooplankton species from thermal stress (Roberts et al., 2010 ), which has been extensively studied in many aquatic organisms (González et al., 2016 ; Xiang et al., 2017 ). Although numerous studies have examined the ecological and physiological responses of aquatic organisms to temperature stress, there is still a dearth of research on transcriptomics.…”
Section: Introductionmentioning
confidence: 99%
“…( 2013 ) found that the upregulation of CuZn‐SOD gene expression in a certain range plays an important role in maintaining the physiological equilibrium of Brachionus calyciflorus . In addition, stress proteins such as heat shock proteins and antioxidant enzymes also play an important role in protecting zooplankton species from thermal stress (Roberts et al., 2010 ), which has been extensively studied in many aquatic organisms (González et al., 2016 ; Xiang et al., 2017 ). Although numerous studies have examined the ecological and physiological responses of aquatic organisms to temperature stress, there is still a dearth of research on transcriptomics.…”
Section: Introductionmentioning
confidence: 99%